Theory and Applications of Distinctive Conformable Triple Laplace and Sumudu Transforms Decomposition Methods (Journal of Partial Differential Equations, 2021)
This article presents some important results of conformable fractional partial derivatives. The conformable triple Laplace and Sumudu transform are coupledwith the Adomian decomposition method where a new method is proposed to solvenonlinear partial differential equations in 3-space. Moreover, mathematical experiments are provided to verify the performance of the proposed method. A fundamental question that is treated in this work: is whether using the Laplace and Sumudutransforms yield the same results? This question is amply answered in the realm of theproposed applications.
Keywords: Riemann-Liouville fractional integral; fractional derivative; Adomian decomposition method; conformable fractional partial derivative; conformable triple Laplace and Sumudu transform.